Higher Education and the Sustainable Knowledge Society: Investigating Students' Perceptions of the Acquisition of Sustainable Development Competences - Cavicchi, Caterina (Frontiers in Sustainable Cities, 2021)
The application of a constructivist approach to competence-based frameworks for sustainable development (SD) in higher education can empower students to become change agents. Acknowledging this development, this paper examines the extent to which an SD-directed master’s programme at an Italian university effectively developed students’ SD competences before and during the COVID-19 pandemic. The study is based on a mixed method approach that includes a survey and interviews in order to a) discuss students’ experiences with pedagogies that emphasize SD competences as learning outcomes and b) analyze students’ perceptions of acquiring SD competences with reference to their experience of internships, project work, and job positions (in the case of graduates). The results show that, among the analyzed SD pedagogies, case studies were perceived to enrich students’ understanding of the complexity of SD issues through collective learning. However, to develop critical thinking, students recognized the need to customize the case studies’ plots. Regarding practical SD activities, internships and project work were perceived as opportunities to network with stakeholders and to develop problem-solving abilities. The pandemic significantly decreased the use of such SD pedagogies, thereby prioritizing self-directed learning and research-based internships. Despite the increase in e-learning events involving stakeholders, the prospect of interacting with them on SD topics was hampered by the limitations of information technology support. Nevertheless, the students’ perceptions of the effectiveness of teaching and learning processes provide recommendations to improve the SD pedagogies and e-learning adopted by higher education institutions.